Tourism Site Infrastructure, Visitor Patronage and Calabar Metropolis - Gloria Mayen Umukoro; Veronica Ebi Odey; Edisua Merab Yta (Universitas Negeri Makassar, 2020)
This study investigates the nature of tourism site infrastructure and how it affects patronage in Calabar Metropolis, Cross River State. The specific objectives of the study are to assess the security level, availability of leisure aid, recreation facilities, quantity and quality of historical artifacts, location ambiance, skilled tour guides and their effect on visitor patronage. The study is supported by Qualitative and inferential research design methods to ascertain the predictability of tourist patronage. A sample of one hundred and twenty-five (125) respondents were systematically selected for the study and questionnaires administered. The multiple nonlinear regression test statistic was deployed for validating the hypotheses developed for the study. Results show that security level, leisure and recreation, historical artifact and requisite accommodation were statistically significant in impacting a positive/direct influence on visitor patronage, while location ambiance and skilled tour guides were not statistically significant. It concludes that changes in visitor patronage can be accounted for by changes in tourist site infrastructure, but that location ambiance and skilled tour guides are not sufficient pull-factors for visitor patronage in Calabar Metropolis. It recommends among other things, government and private sector involvement in archeological research, security facilities, affordable accommodation for activities and oppressive use of mass media in portraying the historical significance of the area.